Creación e implementación de un sistema de costeo ABC para emprendedores reposteros de la ciudad de Loja, provincia de Loja - Loor Ceballos, Gloria Katherine (2023)
This thesis project, Creation and Implementation of an ABC Costing System for pastry entrepreneurs in the city of Loja, Loja province, aims to contribute as a guide that allows pastry chefs and bakers in Loja city to improve the management of their businesses through the application of the correct techniques so they can calculate the price of their products, improve the performance of their accounting processes optimizing resources, correctly valuing the labor. We started with collecting information on all the stages of the accounting process, with their respective accounting documents leading to the financial statements, where you can see the summary of the company's economic activity. It is essential to make all the source documents with the necessary data to be able to calculate more accurately the costs and expenses involved in each process; the calculation of labor according to the experience and skill of the employee has been considered according to historical data of very similar procedures or of similar characteristics. The ABC costing system applied in this work has been carried out based on the records of the Mister Cupcake Loja bakery, where it has been possible to obtain in detail each part of the production process and the details of the activity usually performed by a baker, all this has allowed us to get a reasonably accurate calculation of each stage and results that can be applied in other bakeries in the city of Loja. Keywords: Costs, Expenses, Accounting process, costing system.